2009
DOI: 10.1002/mawe.200900483
|View full text |Cite
|
Sign up to set email alerts
|

Umformende Herstellung von Al/Mg‐Werkstoffverbunden

Abstract: A universal theory for the bonding of metallic materials does not exist. For new material combinations and new joining technologies the bonding properties have to be examined individually. The factors affecting bonding behavior and characteristic like the bond strength have to be investigated. This paper presents a method for generating composites by a forming process and shows innovative possibilities to test and evaluate relevant parameters of the bonding process

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…In addition, there is an opportunity to specifically examine the composite-enhancing effect of a multitude of parameters [4,5,6]. Compared to spin extrusion, the specimens used here are distinguished through a costefficient geometry assuring an economic and statistically ensured analysis of the parameters.…”
Section: Execution and Results Of Lateral Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is an opportunity to specifically examine the composite-enhancing effect of a multitude of parameters [4,5,6]. Compared to spin extrusion, the specimens used here are distinguished through a costefficient geometry assuring an economic and statistically ensured analysis of the parameters.…”
Section: Execution and Results Of Lateral Extrusionmentioning
confidence: 99%
“…A micro structural examination of the interface (Fig. 6) demonstrated that a homogeneous interface is formed between magnesium and aluminum under the given test conditions [5] [6]. …”
Section: Figure 5: Analogy Experiments -Lateral Extrusionmentioning
confidence: 98%
“…Eine weitere Möglichkeit bietet die Ausnutzung des Synergieeffekts bei Werkstoffverbunden 2 . Ein Beispiel hierfür ist die Kombination des leichtesten Konstruktionswerkstoffes Magnesium (ρ = 1,7 g/cm 3 ) mit dem korrosionsbeständigen Standardwerkstoff Aluminium (ρ = 2,7 g/cm 3 ) 3 . Gängige Verfahren zur Herstellung dieser Materialkombination sind beispielsweise das Strangpressen 4 oder das Sprengplattieren 5 .…”
Section: Introductionunclassified
“…Als Referenz diente ein bei 300 8C fließgepresster Aluminium-Magnesium-Verbund ohne Zwischenschicht. Die Ergebnisbewertung wurde anhand der Homogenität der Zwischenschicht, der Anzahl von Fehlstellen, der Schichtausbildung und der Anbindung an die beiden Grundwerkstoffe für den erzielten Verbund durchgeführt [4]. Der beim Querfließpressen auftretende inhomogene Werkstofffluss, der experimentell anhand der gerasterten Proben übereinstimmend zur Finite-ElementeMethode nachgewiesen werden konnte, hat zur Folge, dass die Zwischenfolie nach der Umformung verhältnisgleich zur Oberflächenvergrößerung ausgedünnt wird, Bild 3.…”
Section: Introductionunclassified